Enhancement of the tomato supply and distribution system in the province of Cavite - Arroyave, Diana Victoria Carvajal; Magnaye, Dina C. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
The Province Cavite is the most urbanized province in Metro Manila's peri-urban area with an average population growth rate double that of the Philippine average. Urbanization in this province is taking place in an unplanned way, which impairs the efficiency of Food Supply and Distribution System (FSDS). This scenario demands a comprehensive approach which considers food as a central element in the planning discipline to guarantee the right to food of the people. FSDS involves a combination of activities, functions and relationships from production up to the marketing of a commodity that allows cities to satisfy their food requirements. The study focused on the enhancement of the Tomato Supply and Distribution System (TSDS) in Cavite Province. This necessitates the identification of strategies as inputs in formulating development and spatial planning agenda based on the characterization and mapping of the TSDS and analysis of the system's existing constrains and opportunities utilizing key performance indicators. The indicators analyzed in the study included the relationship of TSDS stakeholders (farmers, traders, wholesalers and retailers); financial capacity of the key TSDS actors; availability of financial and non-financial incentives; rate of land utilization, and the condition/ appropriateness of distribution infrastructure.The study revealed a general fragility of the supply sub-system of the TSDS due to high rate of productive land conversion to residential uses; and the weak bargaining power of farmers compared with other TSDS players. Nevertheless, the distribution side of the TSDS is favored by the availability of good road network and transport infrastructure of the province; active government efforts to strengthen the vertical and horizontal relationships of farmers with the other TSDS stakeholders; a relatively equal sharing of profits and expenditures among the farmers, traders an wholesalers/retailers; and availability of financial and non-financial incentives. The recommended development strategies to enhance the TSDS in the Province of Cavite include the strengthening of cooperatives/associations; conduct of financial management education programs for farmers; and establishment of market information infrastructure. The spatial planning strategies that are proposed to develop the TSDS of Cavite Province cover the promotion of research agenda for the TSDS; certification of tomato farms under the God Agriculture Practices; and strengthening of technology as well as knowledge transfer programs on TSDS.
Thesis (Master of Science Regional Development Planning)--University of the Philippines Diliman
Keywords: Tomato industry -- Philippines -- Cavite Province; Tomatoes -- Philippines -- Cavite Province; Tomato growers -- Philippines -- Cavite Province; Urbanization -- Philippines -- Cavite Province